The Teaching of Philosophy from our Latin American Reality: The Case of Universidad Nacional, Costa Rica - Gómez Torres, Juan Rafael (2018)
To start this essay, we turn to an old question: Is there Philosophy in Latin America? According to Estermann, the knowledge of indigenous peoples is undoubtedly Philosophy, at least in a broad sense if Latin American Philosophy is conceived as the human effort to understand the world (2009), through cosmogonic speculation and questioning or if it is seen as an epistemological, metaphysical, ethical, and political aestheticization process (of course, these terms must be relativized when referring to the indigenous world), which has myth as its starting point and cosmogony as a complex unit that condenses the mythical links (Cassirer, 2012).